Plasmonic nanoprism enhanced quasi-2D Ruddlesden–Popper layered perovskite photodetectors. Issue 3 (17th December 2019) - Ji, Ting; Zhang, Hengkang; Han, Na; Wang, Wenyan; Wu, Bo; Li, Guohui; Fan, Mingming; Li, Zhanfeng; Hao, Yuying; Zhu, Furong; Wu, Yucheng; Cui, Yanxia
Abstract : AuAg-NPrisms@SiO2 were incorporated into quasi-2D perovskite PDs and improved performances were obtained. EQE of 1670%, R of 7.15 A/W and D * of 3.2 × 10 13 Jones were achieved. Crystallinity of the quasi-2D perovskite film was also improved. Abstract : Compared with the three-dimensional (3D) hybrid perovskite materials, the Ruddlesden–Popper layered two-dimensional (2D) perovskites are much more stable due to the introduction of large hydrophobic cations. And they have many important applications in optoelectronic devices. Here, we demonstrate that the performance of the quasi-two-dimensional (quasi-2D) perovskite photodetectors (PDs) can be improved by incorporating a layer of SiO2 coated AuAg-alloyed nanoprisms (AuAg-NPrisms@SiO2 ). Incorporation of AuAg-NPrisms@SiO2 can increase the external quantum efficiency (EQE) values of the device over a broadband wavelength range. Under 532 nm laser illumination at an incident power density of 1 × 10 −4 mW cm −2, the quasi-2D perovskite-based PD with AuAg-NPrisms@SiO2 exhibits a high EQE of 1670% at a low driving voltage of −0.3 V. Responsivity ( R ) and detectivity ( D* ) reach 7.15 A W −1 and 3.2 × 10 13 Jones, increased by 51.2% and 68.4% with respect to the control PD. Studies show that AuAg-NPrisms@SiO2 incorporation can help to form high quality crystalline quasi-2D perovskite films, increase light absorption in the active layer, accelerate exciton dissociation at the interface and facilitate charge transport in the devices. These synergistic effects contribute to the improvement of EQE, R, D* and stability of the device after AuAg-NPrisms@SiO2 doping. This work contributes to the fabrication of low-cost and high-performance PDs.